Nasopharyngeal Migration of Coils Following Embolization of a Traumatic Pseudoaneurysm of the Internal Carotid Artery: A Case Report (2024)
ABSTRACT: Post-traumatic pseudoaneurysms of the internal carotid are a rare but potentially fatal cause of epistaxis; they are associated with fractures of the base of the skull with involvement of the carotid canal. Endovascular management is the preferred therapeutic strategy, with optimal long-term results and low complication rates. Complications may include thromboembolic events, infarction of perforating arteries, and rupture of the pseudoaneurysm. We present a case of a 28-year-old male with a post-traumatic pseudoaneurysm of the internal carotid who was managed with endovascular therapy. A late complication was the extrusion of the embolization material into the nasal cavity and nasopharynx, which was safely and effectively treated through endovascular and endoscopic approaches.